Does capital account liberalisation lead to investment booms in Caribbean economies - Boamah, Daniel...[et al.] ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Examines whether capital account liberalisation stimulates higher capital and financial inflows in Caribbean countries, using data for Barbados, Guyana, Jamaica and Trinidad and Tobago.